AI-Powered Online Buying Using the M Wallet System - ., Devesh (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2023)
An online store with a variety of things that users may need. The system is designed to assist consumers with their shopping and to carry out their purchases. The computer uses the user’s preferences to make purchases. Artificial intelligence building blocks are suggested for the system, ensuring users have a hassle-free purchasing experience. The system also incorporates M-Wallet.The integration of M-Wallet guarantees a positive mobile shopping experience. Because both systems are integrated, users can simply enter their preferences and the system will quickly find the best value for them.